A Vacuum of Norm in the Extension of the 0.5% Final Income Tax Rate for MSMEs: A Legal Analysis of the Principle of Legal Certainty in the Taxation System - Andriyana, Hendra; Hasibuan, Ali Huristak Hartawan; Pratama, Topan Yulia (Journal La Sociale, 2026)
The Final Income Tax (PPh Final) policy of 0.5% for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia serves as a fiscal strategy aimed at simplifying tax administration and enhancing voluntary compliance. However, a legal issue has emerged approaching early 2025, when the validity period of the 0.5% final tax rate under Government Regulation (PP) No. 23 of 2018 expires, while its successor, PP No. 55 of 2022, does not provide any transitional mechanism or explicit extension clause. The absence of a normative framework to regulate this situation has resulted in a legal vacuum (rechtvacuum), creating legal uncertainty and potentially violating the principle of tax legality. This study aims to juridically analyze the legal vacuum in the extension of the 0.5% Final Income Tax rate for MSMEs and to evaluate its implications on legal certainty and taxpayers’ rights protection. The research employs a normative legal method using statutory, conceptual, and historical approaches, supported by relevant primary and secondary legal materials. The findings reveal that the absence of transitional regulation has led to administrative confusion, unequal tax treatment, and a decline in public trust toward the tax authority. The inconsistency between public policy announcements and formal regulations indicates a weakness in normative control within Indonesia’s tax system. Therefore, immediate regulatory intervention in the form of formal written rules is required to ensure legal certainty, prevent maladministration, and maintain the legitimacy of the national tax regime.